EFEKTIFITAS TEKNIK METAFORA DALAM LAYANAN KONSELING KELOMPOK UNTUK MENINGKATKAN PERCAYA DIRI SISWA - Sulistyaningsih, Rahayu (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2018)
The aim of this research is to find out the effectiveness of metaphor technique in group counseling to improve the students? self-confidence. It was a research on the seventh graders? self-confidence of State Junior High School 1 Tembarak, Temanggung. The research is an experimental research of pre-test and post-test of one group design. The subject of the research was chosen by purposive sampling with 13 students of low, average, and high level of self-confidence. The data was analyzed by statistic, non-parametric, with Wilcoxon-signed rank test, with SPSS program 23.00 version for windows. The results indicated that group counseling with metaphor technique was effective to improve the students? self-confidence. It was proven by the difference of post-test score improvement which was higher than the pre-test score. The highest score was 84 or about 78.50%. The average score was 33 or about 25.93%, and the lowest score was 5 or about 28.59%. Besides, the students? self-confidence improvement was signed by the difference of the students? self-confidence aspects and indicators. One of them was the students? bravery to try a new thing confidently.